Prevalence and Associated Factors of Anxiety and Depressive Symptoms Among Bereaved Family Members of Cancer Patients in Korea: A Nation-Wide Cross-Sectional Study. Issue 22 (May 2016) - Jho, Hyun Jung; Choi, Jin Young; Kwak, Kiu Sang; Chang, Yoon Jung; Ahn, Eun Mi; Park, Eun Jung; Paek, Soo Jin; Kim, Kyoung Mee; Kim, Soo Hyun
Abstract : Abstract: Bereaved family members of cancer patient are at risk of having psychological problems such as anxiety and depression. However, prevalence and associated factors of anxiety and depressive symptoms among this population have not been explored in Korea. We conducted a nation-wide cross-sectional questionnaire survey of 3522 bereaved family members of cancer patients who died at 44 hospice palliative care unit (HPCU) in Korea in 2012. The questionnaire comprised the Hospital Anxiety and Depression Scale (HADS) and Good Death Inventory (GDI). Deceased patient's age, sex, primary site of cancer, duration of stay at HPCU, awareness of terminal status, bereaved family member's age, sex, and relation to the deceased were collected from Korean Terminal Cancer Patients Information System. 1121 returned questionnaires were analyzed (response rate, 31.8%). Using a cut-off value of 8 for HADS subscale, the prevalence of anxiety and depressive symptoms was 48.0% and 57.6%, respectively. Mean scores for HADS-A and HADS-D were 7.88 ± 4.87 and 8.91 ± 4.82, respectively. Among the bereaved, older age, being a spouse to the deceased, family members of younger patient, and negative score for a few GDI items were significantly associated with an increased risk of having anxiety or depressive symptoms in the multivariate logistic analysis. In conclusion, we noted the high prevalence of anxiety and depressive symptoms among the bereaved of cancer patients and identified associated factors for these psychological morbidities. Systematic efforts are needed to improve the mental health of the bereaved family members of cancer patients.